2018
DOI: 10.1111/1556-4029.13764
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Self‐Enucleation in an Incarcerated Patient: Case Report and Review of Literature

Abstract: Self-enucleation is a severe form of self-injurious behavior which presents as an ophthalmologic and psychiatric emergency. It is usually known to occur with untreated psychosis, however, there have been reports of self-enucleation across various psychopathologies. We review a case documenting self-enucleation in the forensic setting in a patient with an unusual presentation and cluster of psychotic symptoms. Literature was reviewed using PubMed/Medline databases with key terms: "forensic science," "forensic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…3 Other psychiatric associations include depression, borderline personality disorder, post-traumatic stress disorder and obsessive compulsive disorder. 3,4 They can also be associated with some organic disorders such as neurosyphilis, epilepsy, Lesch-Nyhan Syndrome, dementia, structural brain lesions and even diabetes. [3][4][5] Drugs have been implicated in some cases, including cannabis, stimulants such as amphetamine and cocaine, and hallucinogens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Other psychiatric associations include depression, borderline personality disorder, post-traumatic stress disorder and obsessive compulsive disorder. 3,4 They can also be associated with some organic disorders such as neurosyphilis, epilepsy, Lesch-Nyhan Syndrome, dementia, structural brain lesions and even diabetes. [3][4][5] Drugs have been implicated in some cases, including cannabis, stimulants such as amphetamine and cocaine, and hallucinogens.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 They can also be associated with some organic disorders such as neurosyphilis, epilepsy, Lesch-Nyhan Syndrome, dementia, structural brain lesions and even diabetes. [3][4][5] Drugs have been implicated in some cases, including cannabis, stimulants such as amphetamine and cocaine, and hallucinogens. 4 One study which reviewed 41 cases found that the majority of cases involved young, male schizophrenics, psychotics or those suffering from alcohol or drug abuse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations